User Interface/User Experience Design of Le Mans 24 Hours History Website for Motorsport Education. - Ravielian Azzarin; Pratama Bayu Widagdo (Universitas Negeri Semarang, 2025)
Access to Le Mans 24 Hours endurance racing history content faces limitations in a more structured and comprehensive digital format, although in practice Le Mans 24 Hours brought many innovations and technologies to commercial cars. For example, the book Le Mans: A Century of Passion that archives the 100-year history of Le Mans has only 2500 copies produced, making it out of reach for many. The purpose of this project is to design a user interface (UI) and user experience (UX) website to present comprehensive information about the history of Le Mans 24 Hours as an educational medium. The method used in this study project is a Design Thinking approach with a Design Sprint framework consisting of five stages: Understand, Diverge, Converge, Prototype, and Testing. Then produce a prototype of the